INDIGENOUS PRACTICE: SOME INFORMED GUESSES –SELF-EVIDENT BUT IMPOSSIBLE - Arnon Bar-On, Prof (Social Work/Maatskaplike Werk, 2003)
Ever since Western social work was exported to Africa an ongoing debate has been taking place on whether it fits the African context. Most of this debate, however, has revolved around Western social work’s techniques rather than on its ends, which, being predicated on Western values, are likely to be alien to many Africans. The article outlines the arguments why Africa might require a form of social work of its own and the chances of such indigenisation taking place. It concludes, however, that while indigenisation may be a desirable end, it is probably impossible unless African social workers can engage in reflective learning with their clients. Common sense, presumably a universal trait, suggests that people behave differently in different situations and, as a corollary, that they require different types of knowledge that befit these situations. Most people, for example, conduct themselves differently at home and elsewhere and adapt their clothing and behaviour differently to formal and informal occasions. Equally apparent is that similar differences apply to people who live in different circumstances and, partly as a result, entertain different conceptions of the good. Thus, children in a resource-strapped school, who must share pencils in class, are more likely to develop interdependent outlooks than their counterparts in richer schools. Indeed, so self-evident are such observations that they beg the question why a practical pursuit like social work, as distinguished from more theory-oriented disciplines, must examine them at all? Or is this so? Recent years have seen a sharp rise in social workers being accused of skirting this common sense by ignoring the specific, lived-in experiences of many of their clients and consequently of being largely ineffective. Among these concerns are the negatively labelled "anti-racist", "anti-sexist", "anti-oppressive" and "anti-agist" prescriptions that increasingly imbue Western social work writings, and the more positively labelled "indigenisation" movement that emanates more from developing countries. This article examines the latter’s apprehensions, mainly as presented by African scholars, arguing that while its reasoning is self-evident, effective transformation of this reasoning into professional practice is often impossible. The article that follows this exposition (MW/SW 38(4) pages 311 - 323), by Kwaku Osei-Hwedie, contests this position in maintaining that the development of indigenous African social work knowledge and practices are possible.